2018
DOI: 10.4103/ua.ua_118_17
|View full text |Cite
|
Sign up to set email alerts
|

Is retrograde intrarenal surgery the game changer in the management of upper tract calculi? A single-center single-surgeon experience of 131 cases

Abstract: Introduction:Success of any modality for stone disease needs to be evaluated in terms of Stone Free Rates (SFR), auxiliary procedures needed; complications and follow up. SFR in RIRS is subject to parameters like stone burden, location, number, hardness, composition; calyceal and ureter anatomy; use of ureteric access sheath (UAS); surgeon experience etc.Methods:The aim of this study is to evaluate the efficacy and safety of RIRS for managing upper tract stones. The objectives include evaluating SFR in RIRS in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 10 publications
(12 reference statements)
0
4
0
Order By: Relevance
“…Patients' demographic data are summarized in Table 1.The mean stone size was 13.5 mm (range 7-20 mm). The mean stone sizes were 13.6 (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) 33.8%), and multiple calyces (n=88; 19.4%). Patients' stone characteristics are summarized in Table 2.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Patients' demographic data are summarized in Table 1.The mean stone size was 13.5 mm (range 7-20 mm). The mean stone sizes were 13.6 (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) 33.8%), and multiple calyces (n=88; 19.4%). Patients' stone characteristics are summarized in Table 2.…”
Section: Resultsmentioning
confidence: 98%
“…Percutaneous nephrolithotomy has its own limitations and possible complications, including fever, sepsis, pneumothorax, colonic injury and hemorrhage requiring blood transfusion [17] . On the contrary, in many studies, it was reported that major complications were seen rare, while RIRS complications were seen as lower in Clavien degrees [17] .…”
Section: Discussionmentioning
confidence: 99%
“…The finding that larger stone size is a risk factor for residual stones after RIRS is consistent with previous studies in the literature. 13 Doykov et al showed that larger stone size was associated with a higher incidence of stone residuals (OR = 1.12, 95% CI: 1.006-1.25). 14 Similarly, Zhu et al demonstrated that the risk of residuals increased with moderate to severe hydronephrosis, lower calyceal location, multiple and staghorn calculi, and larger stone size.…”
Section: Discussionmentioning
confidence: 99%
“…Schoenthaler et al reported SFR ranging from 54% to 96% for renal stones smaller than 2 cm after one session and 86% to 92% for renal stones larger than 2 cm after one to four sessions of RIRS [ 7 ]. Another study reported stone clearance for stone size <1.5 cm as 84%, whereas stones >1.5 cm had a clearance rate of 62% [ 18 ]. Contrary to the above study, Lin et al have found RIRS to be a safe and effective treatment option for renal stones between 2 cm and 3 cm with an acceptable SFR of 80.2% [ 19 ].…”
Section: Discussionmentioning
confidence: 99%